The Baluty Ghetto - Štingl, Pavel (Poland : K2 Studio ; Yeti Films ; Czech Television ; Evolution Films, 2008)
Before World War II, Baluty was a feared criminal district of Lodz. Immediately following their occupation of Poland, the Nazis turned the neighborhood into a Jewish ghetto with 160,000 inhabitants. A year later, in the autumn of 1941, five transports of Czech Jews arrived. This group of assimilated Central Europeans finds itself amidst the highly traditional local Hasidic population, which spoke Yiddish - for them, a foreign language. They become witnesses to indescribable torture which they soon are subjected to as well. They are made to suffer by Nazi regulations as well as by the Jewish ghetto council, which hates them for being different. Of 5,000 deportees, only 240 ravaged individuals survived the war. Following the war, the neighborhood was settled by people who had lost their homes. The old houses are now inhabited by poor Poles feared by the outside world. Their life is marked by the stigma of the place.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films